The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s11418-014-0875-3
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic toxicity of Echis carinatus venom: neutralization by Cassia auriculata L. leaf methanol extract

Abstract: Viper bites cause high morbidity and mortality especially in tropical and subtropical regions, affecting a large number of the rural population in these areas. Even though anti-venoms are available, in most cases they fail to tackle viper venom-induced local manifestations that persist even after anti-venom administration. Several studies have been reported the use of plant products and approved drugs along side anti-venom therapy for efficient management of local tissue damage. In this regard, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Snake venoms typically contain hyaluronidase. Adding a hyaluronidase‐inhibitor to a tumescent contravenom solution might limit the extent of venom diffusion beyond the snakebite site and delay systemic absorption of venom and limit the spread of venom within local tissues …”
Section: Discussionmentioning
confidence: 99%
“…Snake venoms typically contain hyaluronidase. Adding a hyaluronidase‐inhibitor to a tumescent contravenom solution might limit the extent of venom diffusion beyond the snakebite site and delay systemic absorption of venom and limit the spread of venom within local tissues …”
Section: Discussionmentioning
confidence: 99%
“…Orchestrated action of locally acting, cell and/or matrix degrading principle toxins (Zn 2+ MPs, PLA 2 s and HYs) present in ECV [ 7 ] are mainly responsible for severe local toxicity of E . carinatus bite.…”
Section: Discussionmentioning
confidence: 99%
“…Over last decade, several studies have been reported the use of plant extracts, phytochemicals and clinically approved drugs to neutralize viper venom induced local toxicity via pre-incubation method. However, few demonstrate the neutralization of local/systemic toxicity both by co and independent injection experiments using murine model [ 7 , 15 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations